A Retrospective Administrative Database Analysis of Suicide Attempts and Completed Suicide in Patients With Chronic Pancreatitis - Chen, Chien-Hua; Lin, Cheng-Li; Hsu, Chung-Y.; Kao, Chia-Hung (Frontiers in Psychiatry, 2018)
Background: The actual incidence rate of suicide attempt and the suicide-related fatality rate (completed suicide) in patients with chronic pancreatitis (CP) have not been mentioned in the literature. Methods: We conducted a nationwide population-based cohort study by analyzing data from Taiwan’s National Health Insurance Research Database (NHIRD) to compare the rate of suicide attempt between a CP cohort and a non-CP cohort. For the study cohort, we identified 17,733 patients (age ≥ 20 years) diagnosed as having CP between 2000 and 2010 from the NHIRD in Taiwan. Beneficiaries with no history of CP were matched with the study cohort at a 2:1 ratio according to age, sex, and index date. To determine the incidence of suicide, all patients were followed until the end of 2011 or until their withdrawal from the Taiwan National Health Insurance program. Results: Patients with CP had an increased risk of suicide attempt, compared with those without CP (adjusted hazard ratio [aHR] = 2.72, 95% confidence interval [CI] = 1,69–4.37). The suicide-related fatality in the CP cohort was higher than that in the non-CP cohort, but the difference was not statistically significant (aHR = 1.21, 95% CI = 0.39–3.78). Conclusion: Our population-based cohort study reveals a close association between CP and subsequent suicide attempt. Compared with the non-CP cohort, the suicide-related fatality was higher in the CP cohort, although the result was not statistically significant. These findings necessitate surveying patients with CP and providing psychological support to prevent suicide.